EKONOMI LUMBUNG DAN KONSTRUKSI KEBERDAYAAN PETANI MUSLIM MADIUN - Arifin, Sirajul; Izzuddin, Muhammad Andik (State Institute of Islamic Studies (IAIN) Salatiga, 2016)
Muslim farmers of Luworo Madiun often suffer from the hegemony of ijon (debtbondage) system. The system which exploits and weakens the farmers can no longer be tolerated, but should be responded through the construction of lumbung (barn; place for rice storage). The lumbung which is constructed next to mosque can become an important asset for creating food security and solving the economic problems of the farmers. However, lumbung asset will not survive or develop if not supported by other assets. The mosque, market, agricultural area, and society itself all are important assets developed by the farmers of Luworo to strengthen the survival and development of lumbung asset. The lumbung then has power not only to build food security but also to strengthen the economic capacity of society. This economic power is developed through the construction of lumbung which gives equal rights to all members, in contrast to the unjust and exploitative ijon system.